CONSUMPTION AND GROWTH EFFICIENCY OF ISA BROWN STRAIN IN PRE-LAYER PHASE ON VARIOUS FEED FORMS - Falah, Fadhilah Dhani Santika; Nugroho, Dimas Fajar; Imaniah, Nida’ul Husna; Wulandari, Afiza (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
This study aimed to evaluate the efficiency of feed consumption and growth in ISA Brown strain during their pre-layer phase, specifically examining the impact of different feed forms: Mash, Crumble, and Pellet. An experimental design with three feed form treatments was employed, measuring feed consumption, body weight gain (BWG), and feed conversion ratio (FCR). Statistical analysis including ANOVA and Duncan’s Multiple Range Test was used to identify significant differences between treatments. The results showed crumble feed led to the highest daily feed intake (2310.00 ± 11.71b g/hen/day), while mash (2075.50 ± 56.31a) and pellet (2080.17 ± 54.48a) were not significantly different from each other but were lower than crumble. Crumble also resulted in the highest BWG (170.17 ± 4.94c g/hen/day), followed by mash (143.13 ± 20.66b), and pellet (109.20 ± 10.80a). FCR was highest (least efficient) in Pellet (19.23 ± 2.22b), while mash (14.78 ± 2.39a) and crumble (13.58 ± 0.42a) showed better and similar efficiencies. It was concluded that crumble feed is most effective in enhancing feed intake, growth, and conversion efficiency in the ISA Brown strain during the pre-layer phase. Keywords: Feed Form, Feed Intake, Growth, ISA Brown, Pre-layer